2021
DOI: 10.3390/app11041369
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sericin on Bone Regeneration in a Streptozotocin-Induced Type I Diabetes Animal Model

Abstract: There is an association between diabetes and impaired bone healing. The purpose of this study was to determine whether sericin had a positive effect on bone regeneration with streptozotocin-induced diabetes in a rat model. Sprague Dawley rats (n = 21) were assigned to one of three groups. A critical-sized bone defect was created on the calvaria. In the sericin group (S group, n = 7), the bone defect was filled with a sericin–gelatin combination, whereas in the gelatin group (G group, n = 7), only gelatin spong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Sericin can increase the expression level of BMP-2 in the macrophage [ 48 ]. The gelatin sponge incorporated with sericin can increase new bone formation compared to the gelatin sponge only graft [ 48 , 49 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Sericin can increase the expression level of BMP-2 in the macrophage [ 48 ]. The gelatin sponge incorporated with sericin can increase new bone formation compared to the gelatin sponge only graft [ 48 , 49 ].…”
Section: Main Textmentioning
confidence: 99%
“…Medication-related jaw bone necrosis is a drug complication induced by impaired angiogenesis [ 50 ]. Diabetic bony lesion has also shown poor vascularity [ 49 ]. PDGF is rich in platelets.…”
Section: Main Textmentioning
confidence: 99%
“…Kim et al [4] reported that 4HR acts as a novel class I histone deacetylase (HDAC) inhibitor, effectively reducing its expression and activity. Hong et al [5] reported that the application of sericin combined with a gelatin sponge significantly enhanced bone regeneration in a diabetic animal model, as evidenced by increased regenerated bone volume compared to control groups. Jang et al [6] reported that 4HR administration reduced root resorption during orthodontic tooth movement in rats, while increasing the expression levels of bone regeneration associated markers, suggesting its potential protective effect against root resorption.…”
mentioning
confidence: 99%